2023
DOI: 10.1093/beheco/arac100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual state on the strength of mate choice in females and males

Abstract: Animals are thought to gain significant fitness benefits from choosing high-quality or compatible mates. However, there is large within-species variation in how choosy individuals are during mating. This may be because the costs and benefits of being choosy vary according to an individual’s state. To test this, I systematically searched for published data relating the strength of animal mate choice in both sexes to individual age, attractiveness, body size, physical condition, mating status, and parasite load.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 175 publications
0
12
0
Order By: Relevance
“…Males expressing lower boldness, on the other hand, may compensate for the lower output per reproductive event by realizing more mating opportunities. A recent meta-analysis supports this hypothesis by showing that attractive males are choosier than unattractive males (attractiveness being defined as traits that signal mate quality) (Dougherty, 2023). If the proposed reproductive strategies (bold males produce few but large broods and less bold males produce many but small broods) yield equal fitness outcomes, this could help maintain among-individual variation in male boldness.…”
Section: Discussionmentioning
confidence: 95%
“…Males expressing lower boldness, on the other hand, may compensate for the lower output per reproductive event by realizing more mating opportunities. A recent meta-analysis supports this hypothesis by showing that attractive males are choosier than unattractive males (attractiveness being defined as traits that signal mate quality) (Dougherty, 2023). If the proposed reproductive strategies (bold males produce few but large broods and less bold males produce many but small broods) yield equal fitness outcomes, this could help maintain among-individual variation in male boldness.…”
Section: Discussionmentioning
confidence: 95%
“…Awareness of these potential effects of male preference helps avoid over‐ or underestimating female preferences. However, two recent meta‐analyses found no evidence that virgin and mated females differ in their choosiness (Dougherty, 2023; Richardson & Zuk, 2022) suggesting an asymmetry in the effects of female mating status on male and female mate choice. Crucially, Richardson and Zuk (2022) found that the majority of studies of female mate choice use virgin females which, combined with the results of this study, suggests that male preferences for virgin females could be influencing our broader understanding of mate choice.…”
Section: Discussionmentioning
confidence: 99%
“…We planned to screen 10 more if at least half of the previous 10 contained relevant articles, but that was not the case for any language. Additionally, we manually included four studies that were not captured by our searches Aguiar Del Matto, 2018;Gómez-Llano et al, 2023;Dougherty, 2023). A pilot conducted for our pre-registration (see Pollo et al 2023) found that these searches retrieved relevant benchmark articles, ensuring that our searches were comprehensive.…”
Section: Methodsmentioning
confidence: 99%